Level of Applying Quality Standards in Technical Education from the Students' Perspective: A Case Study of the Administration and Finance Program in Palestine Technical College, Dir Al Balah - Mervat Moh. Moh. Rady (University of Science and Technology, Yemen, 2018)
The study aimed at investigating students' perspectives regarding the level of implementing quality standards in the program of administration and finance in the Palestine Technical College, Dir Al-Balah. The quality standards include management of the program, program specifications, students' assessment, teachers, students, methods of teaching, scientific research, facilities and equipment. The study also aimed to identify any differences between the participants' responses about the implementation of quality standards in the program of the administration and finance in the Palestine Technical College that are attributable to personal variables (nature of the program, program name, gender, study level). The researcher used the analytical descriptive method, and the study population was (624) students who constitute all the students in the program of administration and finance in the Palestine Technical College, Dir Al-Balah during the first semester 2016/2017 of The study sample (330) female and male students were selected, using stratified random sampling method, according to the variable of program nature (diploma, bachelor). With the assistance of the program management, the researcher distributed the (330) questionnaires. 17 questionnaires were and 313 ones were considered for analysis. One of the major results was that the program was in compliance with quality standards at a moderate degree, except for the standards program administration and teachers which had a higher degree of implementation. There were statistically significant differences between student responses regarding their opinions about the implementation of quality standards in the program of administration and finance in the Palestine Technical College due to the nature of the Program in favor of the diploma. The differences were also attributed to the program name in favor of the diploma of accounting and insurance, to gender in favor of females and to study level in favor of the first level. Keywords: Quality, Quality standards, Technical education.